2007
DOI: 10.1902/jop.2007.070041
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Treatment of Gingival Melanin Hyperpigmentation With Er:YAG Laser: Short‐Term Clinical Observations and Patient Follow‐Up

Abstract: Background: Recently, the erbium‐doped:yttrium, aluminum, and garnet (Er:YAG) laser has been applied effectively for periodontal soft tissue management. The purpose of this study was to report removal of gingival melanin pigmentation using an Er:YAG laser in a short‐term clinical observation. Methods: Five patients with gingival melanin pigmentation participated in this study. Irradiation was performed at 64.0 mJ/pulse (8.5 J/cm2 per pulse) and 10 Hz under water spray in contact mode. Clinical parameters, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 32 publications
6
56
0
1
Order By: Relevance
“…The degree of the pigmentation seems to be related to the differences in melanocyte activity. High levels of oral pigmentation are usually observed in those of African, East Asian, or Hispanic ethnicity [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The degree of the pigmentation seems to be related to the differences in melanocyte activity. High levels of oral pigmentation are usually observed in those of African, East Asian, or Hispanic ethnicity [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Later, the Er:YAG laser was applied in periodontal therapy and many in vitro and in vivo studies have been reported [17][18][19][20][21][22]. Clinical studies evaluating the application of the Er:YAG laser for nonsurgical and surgical periodontal pocket treatment, including root surface debridement [23,24] as well as soft and bone tissue surgeries [25,26], have demonstrated its effectiveness in periodontics [6,27,28]. Recently, several studies demonstrated that the Er:YAG laser has a promising and important role in the field of implant dentistry [7], for gingival and bone tissue management during implant placement procedures [29], as well as for debridement of contaminated implant surfaces and bone defects in the surgical treatment of periimplantitis [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present study, changes in the energy output and surface topography of the quartz tips following ErL contact irradiation on periodontal soft and hard tissues were investigated. Generally, ErL is used with water cooling to facilitate ablation and to prevent thermal damage during ablation of both soft and hard tissues such as gingiva, teeth, calculus, and alveolar bone [42][43][44][45] , but occasionally, ErL is used without water cooling on soft tissues to enhance hemostasis by thermal effects. Therefore, in the present study, the irradiation was conducted with water spray in hard tissue ablation, and irradiation was employed both with and without water spray in soft tissue ablation.…”
Section: Discussionmentioning
confidence: 99%